CRITICAL VIEW ON AUTONOMY HIGHER EDUCATION IN INDONESIA (MAP Observer: Jurnal Penelitian Administrasi Publik, 2021)
To improve the quality and competitiveness in the global education market, several higher education institutions in Indonesia given autonomy through UU No.12 Tahun 2012 that has been applied in early 2013. Frankly, the autonomy of higher education in Indonesia is a multi-level-policy transferred from World Bank ‘Managing Higher Education for Relevance and Efficiency Project in 2005' and a part of obligation Indonesia participation in WTO General Agreement on Trade in Services in 1994. This article would like to give critical insights into whether the deregulation and given autonomy to the higher education institutions in the new public management era will bring better financial management and public service. Using literature studies, we find the most autonomous universities (PTN-BH) manage to gain positive revenue growth and become more exclusive in society.